Status of TIGA activities at the British Isles continuous GNSS Facility and the University of Luxembourg - Hunegnaw, A.; Teferle, F.N.; Bingley, R.M.; Hansen, D.N. (Springer, 2015)
In 2013 the InternationalGNSS Service (IGS) Tide Gauge Benchmark Monitoring (TIGA) Working Group started their reprocessing campaign which proposes to reanalyse all relevant GPS observations from 1995 to the end of 2012 in order to provide high quality estimates of vertical land motion for monitoring of sea level changes. The TIGA Working Group will also produce a combined solution from the individual TIGA Analysis Centres (TAC) contributions. The consortium of British Isles continuous GNSS Facility (BIGF) and the University of Luxembourg TAC (BLT) will contribute weekly minimally constrained SINEX solutions from its reprocessing using the Bernese GNSS Software (BSW) version 5.2 and the University of Luxembourg will also act as a TIGA Combination Centre (TCC). The BLT will generate two solutions, one based on BSW5.2 using a network double difference (DD) strategy and a second one based on BSW5.2 using a Precise Point Positioning (PPP) strategy. In the DD strategy we have included all IGb08 core stations in order to achieve a consistent reference frame implementation. As an initial test for the TIGA combination, all TACs agreed to provide weekly SINEX solutions for a four-week period in December 2011. Taking these individual TAC solutions the TCC has computed a first combination using two independent combination software packages: CATREF and GLOBK. In this study we will present preliminary results rom the BLT reprocessing and from the combination tests.